METODE BERNYANYI TERHADAP MOTIVASI BELAJAR DAN KEMAMPUAN MENGHAFAL PERKALIAN SISWA KELAS III SEKOLAH DASAR - Pinta Uli Panjaitan; Vivi Sahwitri Agutin; Vita Amalia; Risdalina; Destrinelli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the application of the singing method on learning motivation and achievement in memorizing multiplication in grade III elementary school students. The background of this study is based on the low interest and learning outcomes of students in memorizing multiplication, which has an impact on the overall understanding of mathematics material. The singing method was chosen because it is considered capable of creating a pleasant learning atmosphere and making it easier for students to remember material through the rhythm and lyrics of the song. This study uses a quantitative approach with a one group pretest-posttest pre-experimental design. The subjects of the study were 23 grade III students in an elementary school. The instruments used included a learning motivation questionnaire and a multiplication memorization achievement test. The results of the study showed a significant increase in learning motivation and multiplication memorization test results after the application of the singing method. This shows that the singing method is effective in increasing student motivation and learning achievement, especially in multiplication material. Thus, the singing method can be used as an alternative creative and enjoyable learning strategy to improve mathematics learning outcomes in elementary schools.